ANALISIS KEBUTUHAN AWAL STRATEGI PEMBELAJARAN DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA KELAS V SD - Warto Warto (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the initial needs of learning strategies in increasing motivation and learning outcomes of Mathematics for class V Elementary School (SD). The method used in this study is a qualitative descriptive method with research instruments in the form of observation, questionnaires, interviews, and assessment document analysis. The data analysis technique used includes three stages, namely data reduction, data presentation, and drawing conclusions. Based on the results of the initial instrument data analysis, it was found that the motivation and learning outcomes of the fifth grade students at SD Negeri Songgom 01, SD Negeri Songgom 02, SD Negeri Songgom 04 and SD Negeri Songgom 05 in learning mathematics were still low. The average value of student learning motivation is only 62 with the highest score being 82 and the lowest score being 50. While the average score of student learning outcomes is 66.7 in the low category while the highest score is 85 and the lowest score is 45. Low motivation and student learning outcomes are caused by the condition of the learning environment that is not conducive, lack of facilities and infrastructure, lack of support from parents, and the difficulty of using appropriate learning strategies in learning. This research can be used as an initial analysis of the need for appropriate learning strategies in Mathematics learning materials so that students' motivation and learning outcomes can increase.